(untitled) (Philologia, 2021)
In the colonial world, the dividing line between the space of the oppressor and that of the oppressed is clearly visible. In such a setting, there is at times emergence of a no man’s land inhabited by hybrids. This paper investigates the possibilities of an ongoing hybridisation process in j. M. Coetzee’s 1980 novel Waiting for the Barbarians. It gives an overview of the definitions and the use of the term hybrid and presents the possible application of such a term to the Magistrate’s character in the aforementioned novel. Different questionable and ambiguous aspects of the character’s behaviour are taken into consideration, and the conclusion is reached that these indicate that by the end of the novel there are doubtless signs of hybridity in the Magistrate’s character.